Guided Inquiry Learning with Moodle Program to Improve Student Motivation and Learning Outcomes - Luluk Mufidah (Jurnal Pendidikan Sains, 2014)
Pembelajaran Inkuiri Terbimbing dengan Program Moodle untuk Meningkatkan Motivasi dan Hasil Belajar SiswaAbstract: Redox reactions and electrolyte and non electrolyte solution is basic teaching material that contain abstract concepts, causing students’ difficulties in understanding it. Teaching of the re-dox reaction of the electrolyte solution and Non-electrolytes would be better if the student is directed to find the concepts, principles, and laws themselves through inquiry. This study aimed to examine the differences in student motivation and learning outcomes in a redox reaction material and electrolyte solution and non electrolytes with guided inquiry learning, the students taught by experiment and students taught  by using video and animation with Moodle program. This study used a quasi-experimental design. The data were taken using a student’s motivation and motivation questionnaire student learning outcome data were taken using achievement test. Data learning motivation and learning outcomes of students of both classes were tested statistically by t-test. The results showed that: (1) there was no difference in learning motivation among students who are taught by trial and students taught using video and animation with Moodle program, (2) cognitive learning outcomes of students who are taught using video and animation with Moodle courses higher than with students who are taught by experiment.Key Words: guided inquiry, moodle, redox, electrolytes, learning motivation, learning outcomesAbstrak: Reaksi redoks serta larutan elektrolit dan non elektrolit merupakan materi dasar yang bersi-fat abstrak sehingga menyebabkan siswa kesulitan dalam memahaminya. Pengajaran materi reaksi re-doks serta larutan elektrolit dan non elektrolit akan lebih baik jika siswa diarahkan untuk menemukan konsep, prinsip, dan hukum sendiri melalui penyelidikan (inkuiri). Penelitian ini bertujuan untuk menguji perbedaan motivasi dan hasil belajar siswa pada materi reaksi redoks serta larutan elektrolit dan non elektrolit dengan pembelajaran inkuiri terbimbing, antara siswa yang diajar dengan percobaan dan siswa yang diajar menggunakan video dan animasi dengan program Moodle. Penelitian ini menggunakan rancangan eksperimental semu. Data motivasi siswa diambil menggunakan angket motivasi dan data hasil belajar siswa diambil menggunakan tes hasil belajar. Data motivasi belajar dan hasil belajar siswa kedua kelas diuji statistik dengan uji-t. Hasil penelitian menunjukkan bahwa: (1) tidak ada perbedaan motivasi belajar antara siswa yang diajar dengan percobaan dan siswa yang diajar menggunakan video dan animasi dengan program Moodle, (2) hasil belajar kognitif siswa yang diajar menggunakan video dan animasi dengan program Moodle lebih tinggi dibandingkan dengan siswa yang diajar dengan percobaan.Kata kunci: inkuiri terbimbing, moodle, redoks, elektrolit, motivasi belajar, hasil belajar